2022
DOI: 10.1093/ehjcvp/pvac028
|View full text |Cite
|
Sign up to set email alerts
|

Patients selected for dual pathway inhibition in clinical practice have similar characteristics and outcomes to those included in the COMPASS randomized trial: The XATOA Registry

Abstract: Aims To determine the characteristics of patients with coronary artery disease (CAD), peripheral artery disease (PAD), or both, initiating dual pathway inhibition (DPI) using rivaroxaban 2.5 mg twice daily plus aspirin, and to report their clinical outcomes and bleeding rates in clinical practice compared to the COMPASS randomized trial, which provided the basis for using DPI in this patient population. Methods and results XA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…The analysis found a similar incidence of major adverse cardiac events and lower rates of major bleeding as compared to the COMPASS trial. Rates of major adverse limb events were higher, which was consistent with the inclusion of a greater proportion of high-risk patients with PAD [43].…”
Section: Long-term and Community Patient Benefit And Safety Of Dpisupporting
confidence: 70%
“…The analysis found a similar incidence of major adverse cardiac events and lower rates of major bleeding as compared to the COMPASS trial. Rates of major adverse limb events were higher, which was consistent with the inclusion of a greater proportion of high-risk patients with PAD [43].…”
Section: Long-term and Community Patient Benefit And Safety Of Dpisupporting
confidence: 70%
“…In an international multicenter, prospective, real-world study, the annualized incidence rate of MACEs with DPI in patients with CCS and/or PAD was similar to that observed in the COMPASS trial, while the incidence of major bleeding was lower (0.95% per year and 1.67% per year, respectively) [48] .…”
Section: Agesupporting
confidence: 64%
“…The lack of impact on hemoglobin level, renal function, and cardiovascular homeostasis biomarkers observed among our study population confirmed the safety of DPI, among patients with CAD and PAD in a real-world setting. 14 The GDF-15 serum levels have been independently associated with bleeding and death in anticoagulated patients with AF 15 ; however, the role of predictors of bleeding events in other clinical settings still needs to be defined. In patients with CAD, a strong association between GDF-15 and CV death and hospitalization for heart failure (HF) has been shown for GDF-15 serum levels above 1.827 ng/L during 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%